2017
DOI: 10.1002/anie.201705048
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Artificial Potassium Ion Channels Constructed from Pore‐Containing Helical Oligomers

Abstract: Potassium ion channels specifically transport K ions over Na ions across a cell membrane. A queue of four binding sites in the K channel pore plays significant roles during highly selective conduction. A kind of aromatic helical oligomer was synthesized that can selectively bind K over Na . By aromatic stacking of helical oligomers, a type of artificial K channels with contiguous K binding sites was constructed. Such artificial channels exhibited exceptionally high K /Na selectivity ratios during transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 54 publications
0
39
0
1
Order By: Relevance
“…The transmembrane transport properties of the HSP channels were studied according to previous methods 30,31. The co-assembly morphology of the HSPs and lipid bilayers was observed by fluorescence microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The transmembrane transport properties of the HSP channels were studied according to previous methods 30,31. The co-assembly morphology of the HSPs and lipid bilayers was observed by fluorescence microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an important advance has been achieved in the design of directional potassium transport by utilizing zwitterionic peptidic channels . More recently, it has been reported that aromatic helical oligomers can transport K + ions, transmembrane, with high selectivity . In spite of the substantial progress, new synthetic ion channels possessing high K + selectivity are still intriguing for supramolecular chemists.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, synthetic ionophores could potentially alleviate the symptoms of channelopathies 5 , 6 or provide new antibiotic classes able to overcome the growing problem of resistance. 7 Of the wide range of artificial ion channels developed and studied, 8 several show either cation selectivity 9 or anion selectivity. 10 However, a significant challenge in the field is to “switch” any channel activity, 11 so that, like natural examples, activity can be controlled by external stimuli, such as light or chemical messengers.…”
Section: Introductionmentioning
confidence: 99%